A General Approach to Measuring Electoral Competitiveness for Parties and Governments. (11th July 2021) - Cronert, Axel; Nyman, Pär
Abstract: We develop a general approach to measuring electoral competitiveness for parties and governments, which is distinct from existing approaches in two ways. First, it allows us to estimate the actual probability of re-electing the incumbent into office, which lies closer to the theoretical concept of interest than most widely used proxies. Second, it incorporates both pre-electoral competitiveness—that is, the uncertainty about the outcome of the upcoming election—and post-electoral competitiveness—that is, the uncertainty concerning who will form the government given a certain election result. The approach can be applied to, and compared across, a multitude of institutional settings and is particularly advantageous in analyses of multiparty democracies. To demonstrate its full potential, we first apply the approach on 1, 700 local government elections in Sweden. Three advantages over existing approaches are documented: Our election probability measure shows substantial variation over the election cycle, it can be accurately measured for a single party as well as a government, and it is more capable of predicting re-election into office than any previous measure of electoral competitiveness. A second application on 400 national elections in 34 democracies shows that the approach also works well in a more challenging cross-national setting.